Genetics of Malaria Inflammatory Responses: A Pathogenesis Perspective - Penha-Gonçalves, Carlos (Frontiers in Immunology, 2019)
Despite significant progress in combating malaria in recent years the burden of severe disease and death due to Plasmodium infections remains a global public health concern. Nevertheless, only a fraction of infected people develops severe clinical syndromes motivating the search for genetic determinants of malaria severity. Strong genetic effects have been repeatedly ascribed to mutations and allelic variants of proteins expressed in red blood cells but the role of inflammatory response genes in disease pathogenesis has been difficult to discern. This review focused on inflammation-related genes repeatedly associated with malaria namely TNF, NOS2, IFNAR1, HMOX1, TLRs, CD36 and CD40LG. Revisiting reported genetic effects with respect to different malaria clinical phenotypes unveiled that specific genetic variants have dual genetic effects in determining infection and clinical outcomes. This supports a pathogenesis model where pro-inflammatory genetic variants acting in early infection stages contribute to resolve infection but at later stages confer increased vulnerability to severe organ dysfunction driven by tissue inflammation. Human genetics is an invaluable tool to find genes and molecular pathways involved in the inflammatory response to malaria infection but their roles in malaria pathogenesis are still unexploited. Genome editing in malaria experimental models together with novel genotyping-by-sequencing techniques are promising approaches to delineate the relevance of inflammatory response genes in infection and will suggest novel adjuvant therapies for prevention and clinical management of severe malaria.